ANALISIS YURIDIS PENOLAKAN PEMBATALAN AKTA PERJANJIAN PENGIKATAN JUAL BELI (PPJB) HAK ATAS TANAH MELALUI PROSEDUR GUGATAN KE PENGADILAN (STUDI PUTUSAN MA NO. 3703.K/PDT/2016) - Herlina Hasibuan (Universitas Harapan Medan, 2021)
PPJB (Purchase Contract) is and agreement which comes from legal needs in society. A certified PPJB on land rights in an implementation of the principle of freedom in making a contract AJB (Sales Agreement) is made before PPAT (official Empowered to Draw up Land Deeds) so that both the buyer and the seller are bound together to make land rights AJB before a notary. The research used normative method which analyzed legal provisions such as Book III of the Civil Voce and UUJN No. 2/2014 on the Amandement of UUJN No. 30/2004. It also used descriptive analytic method which described, explained, and analyzed the research problems and found the right answer as the solution of the problems. Notarial deed can be done based on article 1338, The legal consideration of the Supreme Court Judge is correct and in accordance with contract law because the seller’s argumentation is that the complaint of the third party is not valid according to legal provisions. Unilateral revocation cannot be carrier out, and it is invalid and illegal since it does not get approval from the other party thow is involved in making the contract.